(x − 3) + (x − 2) + (x − 1) + … + 9 + 10 = 0
2 câu trả lời
Đáp án:
x=1924
Xin hay nhất
Giải thích các bước giải:
3x(4x-3)-2x(5-6x)=0
12x2−9x−10x+12x2=0⇔12x2−9x−10x+12x2=0 ⇔24x2−19x=0⇔24x2−19x=0 ⇔x(24x−19)=0⇔x(24x−19)=0 ⇔[x=024x−19=0⇔[x=024x=19⇔⎡⎣x=0x=1924⇔[x=024x−19=0⇔[x=024x=19⇔[x=0x=1924 Vậy x=0 hoặc x=1924
Xin hay nhất
(x-3)+(x-2)+(x-1)+...+9+10=0
x-3+x-2+x-1+...+9+10=0
(x+x+x)+(-3 + -2 + -1 + ... + 9 + 10)=0
3x+(-3 + -2 + -1 + 0 + 1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10) = 0
3x+4+5+6+7+8+9+10=0
3x+49=0
3x=-49
x=(-49):3
x=-16,3
xin ahy nhất ạ!